Accounting support for employees' motivation as a method of increasing the effective activity of the enterprise - Samchuk K.I. (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2017)
The article analyzes the evolution of scientific perspectives on personnel motivation, defines the concept of "motivation" in economic and legal dictionaries and in educational and methodological literature. The theory of motivation and analytical models of motivation have been investigated, in order to reflect the multifaceted and non-standard nature of the process of motivation and to determine the need for an integrated approach to solving this complex problem. The article presents the grouped motivational types, their characteristics, and the possibilities of organizational support. The classification and content of methods of motivation and stimulation of labor at enterprises, namely: economic, administrative, organizational, production, moral, psychological, social, are given.